The inspiration and authority of the Bible - Warfield, Benjamin Breckinridge, 1851-1921 (London, UK Marshall, Morgan and Scott, 1959)
Includes bibliographical references.
Keywords: Bible -- inspiration; Bible -- evidences, authority, etc